Determination of Chrysene by Gas Chromatography in Selected Soils from Al-Diwaniya Province, Iraq - F. Karam*, Faiq; I. Kadhim, Muqdad (Asian Journal of Chemistry, 2014)
Determination of polycyclic aromatic hydrocarbons compounds in the soil samples is of interest due to their carcinogenic and mutagenic activity in biological systems. The present study focused on the determination concentrations of chrysene in selected soils from Al-Diwaniya province, Iraq. Four sampling sites have been selected of pollution locate on study area. For every sampling site, four sub samples of soils were chooses included: industrial soil, urban soil, cereal grown soil and rural soil, the comparison among these soils were achieved during this study. Soxhlet extraction method was applied to extract the chrysene of soil samples. Under the optimized conditions, low limits of detection and good linearity were obtained. Soil samples were then analyzed by gas chromatography. The analysis of chrysene in real soil samples gave percentage recoveries ranged from 72.23 to 96.11 % with relative standard deviations (RSD) ranged from 1.65 to 4.87 %.